PAYLATER FEATURE: IMPULSIVE BUYING DRIVER FOR E-COMMERCE IN INDONESIA - Luqman Dzul Hilmi; Yeyen Pratika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
E-commerce growth followed by the increasing of digital payment has encouraged the penetration of payment features that aims to attract consumers. The current phenomenon in Indonesia is the existence of Paylater feature. It has a similar function with credit card that allows consumers make credit purchases with a certain limit. Many previous researches indicate that credit card leads to impulsive buying behaviour which makes consumers feel the need to buy immediately by ignoring the utilitarian of purchased product. Because of the same function as credit card, Paylater is presumed the same result. Thus, this study is proposed to examine whether Paylater system drives to impulsive buying behaviour on e-commerce transactions. A total of 158 respondents involved in this study. Using Structural Equation Modelling (SEM) with SmartPLS software, this study found that Paylater and hedonic motivation influence on impulsive buying. However, when Paylater is used as mediator between hedonic and utilitarian motivation on impulsive buying, there is no significant effect.